MODEL DESIGN OF MONITORING WORKPLACE FOR ANALISIS OF CNC MACHINE TECHNOLOGICAL PROCESS - MURČINKO, Jaromír (Trends in education, 2009)
The paper is about designing the monitoring workplace for analysis of CNC machine technological process by means of implementation of multiagent systems. The CNC milling machine Mikron 650 with Fanuc control system was selected for model design. We focused on milling and drilling on mentioned machine.
Keywords: CNC machine; multiagent system; vibration; monitoring.